Pelatihan Metode Jarimatika sebagai Alternatif dalam Pembelajaran Matematika SD - Harfin Lanya; Septi Dariyatul Aini; Sri Irawati (Jurnal Pengabdian Pada Masyarakat, 2020)
JARIMATIKA METHOD TRAINING AS ALTERNATIVE IN ELEMENTARY MATHEMATICS LEARNING. This activity is motivated because of the tendency of the teacher to force students to memorize by looking upward in conveying the concepts of number operations, especially multiplication and division. This can cause students to become bored and result in low math grades. Therefore, we intend to provide training in fingerprinting methods to class teachers at SDN Jambringin II Proppo as an alternative in teaching arithmetic arithmetic operations (addition, subtraction, multiplication, and distribution). The implementation phase of this activity begins with identifying the problem; selection of various learning methods that are suitable for overcoming problems; choosing the Jarimatika method as an alternative; material creation (PPT, handouts and audio-visual video); implementation of activities (training and assistance); and evaluation. The results of this dedication activity are: 1) the teacher gives a positive response to this activity and feels helped to teach arithmetic techniques, especially on multiplication material; 2) the teacher can apply the results of the Jarimatika training to students in the class appropriately.